'When one Dior closes …': The discourse of designer changeovers at historic fashion houses. Issue 3 (1st July 2015) - Jones, Katie Baker
The house of Dior is one of the most successful fashion brands in the world. However, after the sudden death of Christian Dior, in 1957 there was a question as to whether the brand could survive without its founder at the helm. The longevity and success of historic fashion houses has been, in many ways, dependent on finding a head designer capable of carrying on both the legacy and the continued financial success of the brand. Since so much emphasis is placed on the identity and credentials of the head designer of a fashion label, the hiring process is frequently a public affair. As gatekeepers to the fashion world, the media keeps interested parties abreast of the proceedings and subsequent results of the hiring process. A study of the news discourse concerning the search for, announcement, and evaluation of new designer appointments at historically established fashion houses was undertaken to explore the framing of these events in the media. Christian Dior was purposefully selected for this study due to its longevity and the level of media interest in the seven different designers that have held the top design position at the storied house. The New York Times was selected as the site of research due to its history of providing readers with coverage of the international fashion scene in both general interest news categories and its dedicated style sections. A critical discourse analysis of 73 articles utilized iterative, comparative and reflective readings of text to reveal both the socially constructed and the socially constructing elements. The study explores the discursive practices employed by the popular fashion press to report, analyse and validate new designer/artistic director appointments at established fashion houses. How the discourse situated these processes within the larger context and history of the house is also discussed.